Warm, water-depleted rocky exoplanets with surface ionic liquids: A proposed class for planetary habitability - Rachana Agrawal; Sara Seager; Iaroslav Iakubivskyi; Weston P. Buchanan; Ana Glidden; Maxwell D. Seager; William Bains; Jingcheng Huang; Janusz J. Petkowski (Proceedings of the National Academy of Sciences, 2025)
The discovery of thousands of exoplanets and the emergence of telescopes capable of exoplanet atmospheric characterization have intensified the search for habitable worlds. Due to selection biases, many exoplanets under study are planets deemed inhospitable because their surfaces are too warm to support liquid water. We propose that such planets could still support life through ionic liquids: Liquid salts with negligible vapor pressure that can persist on warm planets with thin atmospheres, where liquid water cannot. Ionic liquids have not previously been considered as naturally occurring substances, and thus have not been discussed in planetary science. We demonstrate in laboratory experiments that ionic liquids can form from planetary materials: Sulfuric acid combined with nitrogen-containing organic molecules. Sulfuric acid can be volcanic in origin, and organic compounds are commonly found on planetary bodies. The required planetary surface is water-depleted and must support sulfuric acid transiently in liquid phase to dissolve organics, followed by evaporation of excess liquid—conditions spanning approximately 300 K at 10 −7 atm to 350—470 K at 0.01 atm. Because ionic liquids have extremely low vapor pressures, they are not prone to evaporation, allowing small droplets or pools to persist without ocean-like reservoirs. Ionic liquids’ minuscule vapor pressure at room temperature suggests possible stability on planets with negligible atmospheres, shielded by magnetic fields or rock crevices against harsh cosmic radiation. Ionic liquids can stably dissolve enzymes and other biomolecules, enabling biocatalysis and offering a plausible solvent for life—broadening the definition of habitable worlds.